De l'emphytéose au louage ordinaire par la voie mal éclairée du doute - Frenette, François (Les Cahiers de droit, 1977)
Restrictions upon the emphyteutic holder's rights that are contrary to article 569 C.c. are sufficient justification for depriving a transaction of its emphyteutic character. However it is erroneous, upon rendering such a decision, to pretend that emphyteusis carries with it alienation of property and that a contract so qualified by parties must be considered as an ordinary lease if any doubts arise as to the real nature of the agreement.